Teenage pregnancy as a risk factor for low birth weight: integrative literature review (Research, Society and Development, 2024)
Introduction: Teenage pregnancy is indicated as a risk factor for low birth weight (weight < 2,500 g), is considered a public health problem and has been associated with factors such as education, maternal age, pre-gestational weight, smoking and little prenatal care. Objectives: To investigate the relationship between teenage pregnancy and LBW, listing the risk factors associated with LBW. Methodology: This is an integrative literature review with articles published between 2010 and 2023, in Portuguese and English. The search was carried out in the Virtual Health Library (VHL) database, LILACS/MEDLINE. Seven articles that met the inclusion criteria were selected. Results and Discussion: 71.5% of the studies relate teenage pregnancy to LBW and point out associated factors that contribute to this reality, prevailing among them, in the studies analyzed, smoking, prematurity and insufficient number of prenatal consultations. The number of articles published that study this topic in Brazil points to the factors that must be addressed to minimize one of the public health problems associated with teenage pregnancy, which is LBW. Final Considerations: Teenage pregnancy presents complex challenges that require commitment from all sectors of public health, education, and social assistance to mitigate risks and promote supportive environments for young mothers and their children. It is important that educational practices discuss aspects related to sexuality and reproduction, considering the various factors related to these topics.